2007
DOI: 10.1089/thy.2007.0040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 12 Months Treatment with l-Selenomethionine on Serum Anti-TPO Levels in Patients with Hashimoto's Thyroiditis

Abstract: Our study showed that in HT patients 6 months of Se treatment caused a significant decrease in serum anti-TPO levels, which was more profound in the second trimester. The extension of Se supplementation for 6 more months resulted in an additional 8% decrease, while the cessation caused a 4.8% increase, in the anti-TPO concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0
11

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(90 citation statements)
references
References 18 publications
7
71
0
11
Order By: Relevance
“…In addition, based on the data from two studies, the beneficial effect of selenium supplementation was confirmed regarding the mood of the patients [126]. Brief characteristics of the most important prospective clinical studies [98,122,[127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144] concerning the efficacy of supplementation with selenium in benign thyroid diseases, in particular autoimmune diseases, are presented in Table II.…”
Section: ) Short Characteristics Of the Most Important Clinical Trimentioning
confidence: 99%
“…In addition, based on the data from two studies, the beneficial effect of selenium supplementation was confirmed regarding the mood of the patients [126]. Brief characteristics of the most important prospective clinical studies [98,122,[127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144] concerning the efficacy of supplementation with selenium in benign thyroid diseases, in particular autoimmune diseases, are presented in Table II.…”
Section: ) Short Characteristics Of the Most Important Clinical Trimentioning
confidence: 99%
“…1,2 By strict criteria, it is a histologic diagnosis that was first described by Hakaru Hashimoto, a Japanese surgeon working in Berlin, Germany. 3 The cause of HT is thought to be a combination of genetic susceptibility and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…This result was in accordance with those observed in clinical trails. Supplementation of 200 μg Se per day suppressed anti-thyroperoxidase antibody (TPOAb) levels in patients with AIT in low dietary Se intake [7], in mild selenium deficiency [3], and in a borderline Se sufficient region [4]. There was an additional decrease of TPOAb titers with the extension of Se supplementation lasted for more 3 or 6 months [3-5, 7, 14].…”
Section: Discussionmentioning
confidence: 99%